Psychedelic Fauna for Psychonaut Hunters: A Mini-Review - Orsolini, Laura; Ciccarese, Michela; Papanti, Duccio; De Berardis, Domenico; Guirguis, Amira; Corkery, John M.; Schifano, Fabrizio (Frontiers in Psychiatry, 2018)
Currently different classes of psychoactive substances are easily available for abuse, including several hundred novel psychoactive substances (NPS). Some of these drugs occur naturally in plants and animals or are chemically modified from plant or animal compounds and have been abused by humans over millennia. Recently, the occurrence of a new ‘drug culture’ (e.g., psychonauts) who consume a great variety of NPS with hallucinogenic/psychedelic properties, facilitated the development of a new ‘psychedelic trend’ towards the consumption of substances contained in some species of animals (‘psychedelic fauna’). The present review aims at providing an overview of the most commonly abused ‘psychedelic animals’, by combining a dual search strategy coming from online psychonauts’ experiences and English literature searches on the PubMed/Medline Google Scholar databases. A multilingual qualitative assessment on a range of websites and online resources was performed in order to identify a list of animals who possess some psychoactive properties and could be abused by humans for recreational purposes. Several species are implicated (i.e., ants, amphibians, fish). Routes of administration depend on the animal, substance included, metabolism, toxicity and individual, social and cultural variability. Online purchase and access are easy through tourism-related search strategies (‘frog trip”, ‘help of charmer snake’, ‘religious trip’).